PROSPEK PENERAPAN ZAKAT PENGURANG PAJAK PENGHASILAN SEBAGAI ALTERNATIF KEBIJAKAN FISKAL DI INDONESIA - Ma’mun, Mansur TB (Economic Faculty, Attahiriyah Islamic University, 2017)
The purpose of this research was to determine the effect of zakat to the state revenue if zakat is managed by the State and Prospects for Application of zakat subtracting from income tax as an alternative fiscal policy in Indonesia. This research will use descriptive qualitative method, through the study of the library (Library Research) and field observations (Field research). The results of this research are from the second year of Hijrah, Zakat and Sadaqah has become a major income of the state. The management of Zakat effectively and professionally materialized in the 9 th of after Hijriyah, when Islam had sturdy, had expanded territory and people convert to Islam When the rules of zakat has been arranged which includes; zakat collection system, the limits of charity and alms percentage rates for different goods, as well as the determination of the payroll system (rights) of officer charity. Discussion and critical analysis are described in the article. Keywords: Zakat, pajak penghasilan, kebijakan fiscal